Fisheries and aquatic habitat investigations in the Mackay river watershed of northeastern Alberta ... - Bond, W. A.; Orr, M. R.; Rudy, D.; Miller, D.; Machniak, K. (University of Alberta Library, 1980)
The MacKay River basin is the largest basin on the west side of the Athabasca in the Athabasca Oil Sands region. The lower parts of this basin are part of the lease holding of Syncrude Canada Limited and this project was supported and partially funded by Syncrude. The general objective of this study was to describe the baseline states of the fish component of the MacKay River watershed. This study was part of a broadly based fisheries investigation of the Athabasca River and selected tributaries in the oil sands region of northeastern Alberta. Please refer to the following AOSERP research reports for more fisheries information: Nos. 26 and 76 (Muskeg), 36 (Clearwater), 61 (Steepbank), 84 and 89 (Athabasca), and 92 (Christina, Gregoire, and Hangingstone). ...